The Effect Of Taxpayer Services And Public Service Accountability On Increasing Taxpayer Compliance In Paying Motor Vehicle Tax - Tania Auliana Yahya; Maman Nurochman; Lilis Kartika (LPPM Universitas Sebelas April, 2021)
The essence of this problem is taxpayer compliance in paying motor vehicle taxes at the Sumedang Regency SAMSAT Office. The purpose of this study was to determine the effect of mobile Samsat services and public service accountability on increasing mandatory compliance in paying motor vehicle taxes at the Sumedang SAMSAT Office. This study uses quantitative methods. The number of samples in this study were 100 respondents using random sampling method. The analysis used is multiple linear regression analysis. Data processing using the SPSS for windows 25 program. The results showed that the mobile samsat service and public service accountability had a simultaneous and significant effect on the compliance of motorized vehicle taxpayers in Sumedang Regency. This is indicated by the regression equation Y = 16,090 + 0,461X1 + 0,199.X2 + 3,178 the probability value is less than 0.05, and the Fcount value is greater than Ftable. accountability of public services to the compliance of motorized vehicle taxpayers is 45.9%. Furthermore, according to the results of the t-test, mobile Samsat services have a significant effect on the compliance of motorized vehicle taxpayers as seen from tcount > ttable (2,649>1,660). While the accountability of public services does not affect the compliance of motor vehicle taxpayers because tcount < ttable (1,298 <1,660).